Treatment of acromioclavicular joint dislocation with looped steel plate and clavicular hook steel plate: recent therapeutic observation - Li, Dingtao; Zhang, Zhanshan; Wang, Xiaodong (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the clinical efficacy of Endobutton-looped steel plate and clavicular hook steel plate in the treatment of acromioclavicular joint dislocation. Method: The retrospective case-control study was conducted at the Baoding Forensic Hospital, Hebei University, China and comprised data from January 2022 to June 2023 of adult inpatients of either gender with acromioclavicular joint dislocation. The data was divided into intervention group A and control group B. Group A patients had been treated with Endobutton-looped steel plate, while those in group B had been treated using clavicular hook steel plate. Clinical efficacy, clinical indicators, Karlsson score for shoulder joint function, range of motion of the shoulder, and complications during 6-month follow-up were compared between the groups. Data was analysed using SPSS 26. Results: Of the 50 patients, there were 25(50%) in group A; 15(60%) males and 10(40%) females with mean age 37.75±6.24 years (range: 19-58 years) and mean dislocation-to-visit time 2.52±0.61 days (range: 0-7 days). There were 25(50%) patients in group B; 16(64%) males and 9(36%) females with mean age 38.24±6.30 years (range: 18-59 years) and mean dislocation-to-visit time 2.47±0.58 days (range: 0-6 days). The groups showed no significant differences (p>0.05). Clinical efficacy of group A was higher than that of group B (p<0.05). Group A showed shorter surgical duration and incisional length, and lower average treatment cost compared to group B(p<0.05). The shoulder joint function in group A was significantly better than group B (p<0.05). Post-treatment, the range of motion of abduction, external rotation and internal rotation in group A were superior to group B (p<0.05). Complications in the two groups showed no significant difference (p>0.05). Conclusion: Compared to clavicular hook steel plate, Endobutton-looped steel plate presented higher clinical efficacy, shorter surgical duration, smaller incision and lower treatment cost, which promoted the recovery of shoulder joint function and contributed to high therapeutic safety. Key Words: Looped, Steel, Plate, Clavicular, Hook, Acromioclavicular joint, Dislocation.